2016
DOI: 10.3109/15376516.2016.1158892
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA damage in car spray painters exposed to organic solvents by the high-throughput comet assay

Abstract: Occupational exposure as a painter is associated with DNA damage and development of cancer. Comet assay has been widely adopted as a sensitive and quantitative tool for DNA damage assessment at the individual cell level in populations exposed to genotoxics. The aim of this study was to assess the application of the high-throughput comet assay, to determine the DNA damage in car spray painters. The study population included 52 car spray painters and 52 unexposed subjects. A significant increase in the %TDNA med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Only limited data were found in the literature that demonstrates health impacts experienced by auto body shop workers from VOCs and other hazardous chemicals used in auto body basecoat products. A 2016 study concluded that occupational exposure as a car spray painter was associated with DNA damage and the development of cancer (Londono-Velasco et al, 2016). Another study demonstrated that the use of appropriate personal protective equipment and good workplace hygiene were associated with reduced risk of symptoms of neurotoxicity in solvent-exposed vehicle spray painters (Keer et al, 2018).…”
Section: Social Impact Evaluationmentioning
confidence: 99%
“…Only limited data were found in the literature that demonstrates health impacts experienced by auto body shop workers from VOCs and other hazardous chemicals used in auto body basecoat products. A 2016 study concluded that occupational exposure as a car spray painter was associated with DNA damage and the development of cancer (Londono-Velasco et al, 2016). Another study demonstrated that the use of appropriate personal protective equipment and good workplace hygiene were associated with reduced risk of symptoms of neurotoxicity in solvent-exposed vehicle spray painters (Keer et al, 2018).…”
Section: Social Impact Evaluationmentioning
confidence: 99%
“…It was reported that benzene within the range of 31.5 to 57.3 μg•m -3 can lead to health risks, such as leukemia (D. . Occupational exposure to organic solvent for sprayers has been associated with DNA damage and even caused cancer (Londoño-Velasco et al 2016). ARIs administrators generally provide personal protective equipment, such as respirator masks and allwrapped work clothes, with a certain prevention for sprayers.…”
Section: Introductionmentioning
confidence: 99%
“…Painting activity is giving work to more than 16,000 employees only in Italy. Several studies evaluated the potential adverse effects of exposure to toluene, xylenes, ethylbenzene, styrene and paints in painters, and they showed mainly oxidative and genotoxic effects [ 6 , 11 , 12 , 13 , 14 , 15 ]. In particular, DNA damage by comet assay, but not micronuclei induction was found by Moro et al [ 12 ] on lymphocytes of industrial painters exposed to low toluene levels.…”
Section: Introductionmentioning
confidence: 99%